Complex surface structure of (110) terminated strontium titanate nanododecahedra. Issue 37 (9th September 2016) - Crosby, Lawrence A.; Kennedy, Robert M.; Chen, Bor-Rong; Wen, Jianguo; Poeppelmeier, Kenneth R.; Bedzyk, Michael J.; Marks, Laurence D.
Abstract : Surface at the nanoscale represented as a polyhedral model of a (3 × 1) reconstruction. Abstract : The surface structure of (110) faceted strontium titanate nanoparticles synthesized via solvothermal method has been resolved using high-resolution electron microscopy (HREM). We demonstrate that the surface is a titania-rich structure containing tetrahedrally coordinated TiO4 units similar to the family of ( n × 1) reconstructions observed on (110) surfaces of bulk crystalline strontium titanate. When compared with prior results for (001) terminated strontium titanate single crystals made with traditional transmission electron microscopy (TEM) sample preparation techniques, the results demonstrate that many models for oxide nanoparticles need to be revisited. This work serves as a reminder that attention must be paid to the surface of nanoparticles. Even with a simple perovskite as the starting point the end result can be very complex. As more materials are synthesized on the nanoscale, this will become increasingly important to take into consideration.